THE EFFECT OF WORKING CAPITAL, WORKING CAPITAL TURNOVER AND THE COMPANY'S SCALE TO THE PROFITABILITY OF AUTOMOTIVE COMPANIES IN INDONESIA - Estuti Fitri Hartini; Windarti - - (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2019)
The working capital, working capital turnover, and company scale are numbers of factors that are thought to be relatively large in influencing profitability in automotive companies on the Indonesia Stock Exchange in 2013-2017. To prove the influence of all three, this research was conducted with the aim to determine the effect of working capital, working capital turnover and company scale on profitability in automotive companies listed on the Indonesia Stock Exchange in 2013-2017. The study was conducted by taking data at www.idx.co.id by taking 6 automotive companies as a sample of a total population of 12 automotive companies at a 5% error margin. The research was conducted quantitatively, namely by describing the research data and conducting inference analysis. Multiple regression analysis is used as an analysis tool while hypothesis testing is done by t-test. The research concludes working capital has a significant influence on profitability; Working capital turnover does not have a significant effect on profitability; company scale does not have a significant effect on profitability. Keywords: Working Capital, Working Capital Turnover, Company Scale, Profitability